MENGEKSPLOR BAKAT DAN MINAT SISWA MELALUI RAGAM SENI DI SEKOLAH DASAR - Atmijaya, Rakhmatika; Andaryani, Eka Titi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Exploring students' talents and interests through various arts in elementary schools (SD) is research using the qualitative research method